TANGGUNG JAWAB PELAKU USAHA DALAM TRANSAKSI E-COMMERCE DITINJAU BERDASARKAN HUKUM PERIKATAN - Siregar, Dedi Dewantara (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
Abstract       The problem in this research is Legality of E-Commerce Transaction. Based on Engagement Law and how to the responsibility and the sanctions who given by the suppliers for disadvantage of the consumers in E-Commerce Transaction. For this E-Commerce Transaction, the consumers are too risky for disadvantage, because the transaction is not to do for two sides. Then the risk are conduce of the fraudulence, such as: the mistaken of the products, and inappropriate agreement with the suppliers. This research used Normative Law or Library Law Research based on Secondary data such as from Literature of the legislation. Legality of E-Commerce Transaction based on KUHPdt used Engagement Law Concept based on internet this is the only media for the transaction it is the one condition of the agreement was arranged in Article 1320 KUHPdt and Pasal 1338 for arranged the freedom of the contract. In the E-Commerce transaction, the suppliers it could be accused by Institution of the Consumer Dispute Resolution if the consumers are received the mistaken products, the fraudulence and inappropriate agreement who given disadvantages. This case could be accused in Information Legislation and Electronic Transaction  Article 38 paragraph (1) and Article  45 Constitution Number 8 in 1999 of Consumer Protection.